(untitled) (REMUNOM, 2023)
Aging does not mean being or being sick, but that you need care due to changes over the years. However, it is verified that the elaboration of strategies is one of the great challenges to be faced by Public Health Policies, these actions depend on an integral look to promote the quality of life, being fundamental the nursing care to follow a line of care with excellence and quality for each patient. In view of this, this article defined the objective of describing the practices of Nursing in the Basic Health Unit to offer a humanized service to the elderly in the Basic Health Units. This study was based on a bibliographic review and qualitative studies to describe the theme. When addressing the issues of aging and its challenges for the health of the individual, it was perceived the need to draw a line of quality and excellence care through Nursing professionals in a humanized way in Primary Health Care (PHC), which is the gateway to welcome elderly people for the prevention, promotion, recovery and maintenance of health, the importance of these care professionals and their various contributions within the Unified Health System (SUS). It was also emphasized that the increasing rates of people over 60 years of age compared to other age groups refer to a holistic view and the understanding that changes and public policies must adapt, employing strategies for better structuring, application of changes and innovation in the care model, based on the PHC principle. It also mentions the Human Rights and the Elderly, which need greater protection within society, excluding inequalities and discrimination. From the analysis built through this, it is considered that the nurse has a very important role in the implementation, dissemination and transfer of information about humanization within the PHC, because in addition to direct contact with older patients, they closely assess all the difficulties and changes faced throughout life.